Factors Associated with Callus Formation in the Plantar Region through Gait Measurement in Patients with Diabetic Neuropathy: An Observational Case-Control Study - Ayumi Amemiya; Hiroshi Noguchi; Makoto Oe; Kimie Takehara; Yumiko Ohashi; Ryo Suzuki; Toshimasa Yamauchi; Takashi Kadowaki; Hiromi Sanada; Taketoshi Mori (Sensors, 2020)
Callus has been identified as a risk factor leading to severe diabetic foot ulcer; thus, it is necessary to prevent its formation. Callus formation under the first, second, and fifth metatarsal heads (MTHs) is associated with external forces (pressure and shear stress) during walking. However, the gait factors increasing the external forces remain undetermined. Thus, this study aims to identify the factors increasing the external forces to prevent callus formation. In 59 patients with diabetic neuropathy wearing their usual shoes, the external forces, and the lower extremity joint angles were measured using MEMS force sensors and motion sensors. The external forces and their relationship with the lower extremity joint angles and footwear size were determined. Risk factors causing high external forces on the first MTH included small flexion of the knee joint (p = 0.015) and large ankle pronation motion (p = 0.034) to obtain propulsion. For the second MTH, wearing excessively long footwear was identified (p = 0.026). For the fifth MTH, high external force was related to tight width footwear (p = 0.005). An effective intervention for preventing callus formation for the first MTH would involve assisting the push-off foot motion using rocker-sole footwear or gait training. For the second and fifth MTHs, wearing appropriate size footwear would be effective.